Impact of Educational Infrastructure on Educational Outcomes A Mediation Analysis of Teaching-Learning Environment in Online Tourism Education in India - Jayswal, Dinesh Kumar; Mishra, Jitendra Mohan (Bali Journal of Hospitality, Tourism and Culture Research, 2025)
The present study aimed to examine whether and to what extent the educational outcomes of online tourism education were influenced by the availability of educational infrastructure facilities, and whether this influence was mediated by online teaching and learning environment. A conceptual research model was developed by integrating and synthesising, extensive literature review of theories in the field.  A quantitative correlational study using a predictive design and multivariate analysis method was employed. A sample of 644 students studying in higher educational institutions across India were employed through survey based on a stratified random sampling method. The factor analysis was employed for factor exploration under the key dimensions concerning online tourism education. Structural Equation Modelling analysis was employed to examine the possible relationship between and mediating effect, among the variables. The findings revealed statistically significant relationships between educational infrastructure and educational outcomes through mediation effect of teaching-learning environment. The results revealed educational infrastructure having a significant positive effect on teaching learning environment (β = 0.864), emphasizing the importance of educational infrastructure in tourism educational institutions. However, a direct negative influence of educational infrastructure on educational outcomes was observed (β = - 0.232), suggesting possible additional factors. Interestingly, educational infrastructure was found to significantly enhance educational outcomes, but indirectly, through teaching-learning environment (β = 1.139). This highlighted the crucial role of infrastructure in fostering positive educational outcomes. The findings underscore the complexity of factors shaping the educational landscape, necessitating educational planning and interventions. The study concludes by suggesting the advancement of educational and information and communication technology infrastructure to assist tourism students in their pursuit of online tourism education and a fruitful career.